(untitled) (Colombia Medica, 2006)
Introduction: It is important to study the smoking habit epidemiology in those of humans, which are in the process of academic formation. Those groups will be in the future agents of change in our community and in the case of people involved in the health areas; they are going to deal with risk factors related to chronic diseases. In 2004, the same questionnaire of other study carried out in 2003 was applied in students of programs operating during the day time and enrolled in the first semester, the questionnaire was done during the second half of the year; the purpose was to know the characteristics of the smoking habit in this population and to have a data base for future studies. Methods: This transversal study was done by applying a self responded questionnaire addressed to students of the day time journey and enrolled in the first semester from August to November of 2004. Results: The questionnaire was fulfilled by 1186 (89.6 %) out of 1324 students with criteria to be included in the study. A proportion of 23.2% of students were classified as smokers, with sporadic or habitual habit, and 4.4% of students were classified in the group of ex-smokers. There was a significant difference between males (34.2%) and females (18.2%). According to the group of age, those younger than 17 years old had the lowest proportion of smokers. Despite of non significant differences, the group older than 22 years old had the highest proportion of smokers. Comparing between academic programs, those students from social areas different to health had the highest rate of prevalence. Those students enrolled in programs related to the human airways had the lowest prevalence. Discussion: The prevalence of smokers in this group of study is similar to the rate reported in the general population and studies developed in university students. A bias of no response was confirmed in the study of 2003. Those students from academic programs related to the respiratory airways had lower rates of smokers, and this should be confirmed in other studies.